Food Choices in the Context of Globalizing Food Options among Adolescents in Rural Southern India. Issue 4 (4th July 2022) - Jones, Rebecca E.; Patil, Shailaja; Datar, Ashlesha; Shaikh, Nida I.; Cunningham, Solveig A.
ABSTRACT: Changes in food choice often accompany globalization and economic growth. These changes have not been well documented in rural settings and among young people. To advance research on food choice, we demonstrate adolescents' selection of local vs.non-local foods in a rural area of India where globalization is just reaching. A representative sample of 237 school-going adolescents in a village in Southern India completed a survey in 2019 to understand how adolescents decide among foods traditional to the area and foods arriving from other parts of the country and the world. Adolescents most frequently consumed local foods but also occasionally consumed non-local items. In hypothetical scenarios, 81% of the adolescents reported being most interested in substituting local foods with non-local foods if they were to have more money. Among the few who currently consumed non-local snacks and drinks, very few would be willing to replace them with local alternatives, particularly if they were to have more money (snacks: 10% and drinks: 5% respectively). Overall, adolescents were most interested in switching to non-local items when considering fruits, vegetables and snacks. As India faces the dual burden of undernutrition and overnutrition, understanding the changing food environment may help inform efforts to improve nutrition.